2017
DOI: 10.3389/fphar.2017.00216
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicines Attenuate Acute Pancreatitis: Pharmacological Activities and Mechanisms

Abstract: Acute pancreatitis (AP) is a commonly occurring gastrointestinal disorder. An increase in the annual incidence of AP has been observed, and it causes acute hospitalization and high mortality. The diagnosis and treatment guidelines for AP recommend conservative medical treatments focused on reducing pancreatic secretion and secondary injury, as a primary therapeutic approach. Unfortunately, the existing treatment options have limited impact on the incidence and severity of AP due to the complex and multifaceted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 167 publications
(237 reference statements)
1
33
0
Order By: Relevance
“…It has been used to treat cardiovascular and inflammatory diseases clinically in China for a long time [14]. It has recently found that TMP can ameliorate the damage to pancreas and intestine caused by AP [15,16]. However, the exact mechanism underlying the effect of TMP in AP has not been completely addressed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to treat cardiovascular and inflammatory diseases clinically in China for a long time [14]. It has recently found that TMP can ameliorate the damage to pancreas and intestine caused by AP [15,16]. However, the exact mechanism underlying the effect of TMP in AP has not been completely addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Trypsin can activate additional pancreatic zymogens and protease zymogens, and regulate the proteolytic processes and function of pancreatic exocrine . It was reported that an excessive activity of trypsin could trigger the autodigestion of pancreatic tissues and result in pancreatitis and possible death .…”
Section: Introductionmentioning
confidence: 99%
“…; however, most TIs are proteins in nature . Historically, many traditional Chinese medicines (TCMs) have demonstrated their efficacy in pancreatitis treatment , and some of them have proved to have trypsin inhibitory activity . These facts demonstrated that TCMs could be an important potential source of TIs.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of severe acute pancreatitis includes surgery and non-surgical measure. At present, it is thought that better effects of treatment can be achieved by combining rhubarb extracts or compound rhubarb preparation to medical treatment, which can effectively relieve clinical symptoms, reduce complications and mortality [3]. In this paper, the effects and mechanisms of emodin, a major effective ingredient of rhubarb, in the treatment of severe acute pancreatitis is reviewed.…”
Section: Introductionmentioning
confidence: 99%